Miniaturised visible and near-infrared spectrometers for assessing soil health indicators in mine site rehabilitation - Shen, Zefang; D'Agui, Haylee; Walden, Lewis; Zhang, Mingxi; Yiu, Tsoek Man; Dixon, Kingsley; Nevill, Paul; Cross, Adam; Matangulu, Mohana; Hu, Yang; Viscarra Rossel, Raphael A (2022)
Mining can cause severe disturbances to the soil, which underpins the viability of terrestrial ecosystems. Post-mining rehabilitation relies on measuring soil properties that are critical indicators of soil health. Soil visible–near-infrared (vis–NIR) spectroscopy is rapid, accurate, and cost-effective for estimating a range of soil properties. Recent advances in infrared detectors and microelectromechanical systems (MEMSs) have produced miniaturised, relatively inexpensive spectrometers. Here, we evaluate the spectra from four miniaturised visible and NIR spectrometers, some combinations, and a full-range vis–NIR spectrometer for modelling 29 soil physical, chemical, and biological properties used to assess soil health at mine sites. We collected topsoil samples from reference, undisturbed native vegetation, and stockpiles from seven mines in Western Australia. We evaluated the spectrometers' repeatability and the accuracy of spectroscopic models built with seven statistical and machine learning algorithms. The spectra from the visible spectrometer could estimate sand, silt, and clay with similar or better accuracy than the NIR spectrometers. However, the spectra from the NIR spectrometers produced better estimates of soil chemical and biological properties. By combining the miniaturised visible and NIR spectrometers, we improved the accuracy of their soil property estimates, which were similar to those from the full-range spectrometer. The miniaturised spectrometers and combinations predicted 24 of the 29 soil properties with moderate or greater accuracy (Lin's concordance correlation, ρc≥0.65). The repeatability of the NIR spectrometers was similar to that of the full-range, portable spectrometer. The miniaturised NIR spectrometers produced comparably accurate soil property estimates to the full-range portable system which is an order of magnitude more expensive, particularly when combined with the visible range sensor. Thus, the miniaturised spectrometers could form the basis for a rapid, cost-effective soil diagnostic capacity to support mine site rehabilitation and deliver significant positive economic and environmental outcomes.